'Torn in two': Experiences of Mothers Who Are Pregnant when Their Child Is Diagnosed With Cancer. (October 2022) - Davies, Jenny; O'Connor, Moira; Halkett, Georgia K. B.; Kelada, Lauren; Bosco, Anna Maria; Gottardo, Nicholas G
Mothers of children diagnosed with cancer have been shown to experience high rates of psychological distress and poor physical health. Pregnancy further increases the healthcare needs of mothers due to the marked physiological changes and psychological adaptations. Our study aimed to explore the experiences of mothers who were pregnant and/or had a baby while their older child was receiving treatment for cancer. Our study employed a qualitative description methodology using semi-structured interviews. Participants were recruited from across Australia via notices on social media sites and the distribution of flyers. The sample comprised 13 mothers who were pregnant and/or had a baby and had a child diagnosed with cancer who was under 17 years old. Thematic analysis was used to analyse the data from which six themes were identified: (1) an impossible balancing act, (2) mother's health and well-being, (3) creating certainty: birthing plans, (4) a bit of sunshine and a time to rest, (5) challenges of caring for the baby and (6) an unenviable position: doing my best versus feeling guilty. Our study demonstrates the additional challenges faced by mothers who are pregnant while their child is receiving cancer treatment. There is a need for a comprehensive and coordinated program that provides pregnant mothers with practical and psychological support. The implementation of such a program has the potential to improve health outcomes for all family members, particularly the mother and their newborn.